The impact of COVID-19 on the tourism sector in Indonesia - Aninda Restikadewi; Evandi Syahrul Ramadhan; Ayya Agmulia Asmarani Islam (Universitas Sebelas Maret, 2021)
The purpose of this research is to find out how the COVID-19 pandemic impacts the Indonesian tourism sector. By investigating some secondary sources, we find that the number of tourist arrivals in Indonesia fell by 71 percent during the pandemic. In addition, foreign exchange earnings through industry and tourism in 2020 decreased by 81 percent at 3.2 billion compared to 2019 of 16.9 billion. On the other hand, this study found that government policies such as social restrictions taken by the government greatly affected the Indonesian tourism sector. The tourism sector that is most affected is the sector that is directly related to the presence of foreign tourists and domestic tourists, such as MSMEs, hotels, and the culinary industries. The government needs to periodically evaluate the policies taken so that the tourism sector can also continue to run as it should while still complying with health protocols.